A literature review on the benefits of the use of Books in early child development: an alternative during the COVID-19 Pandemic - Jesús David Cortés-Gil; Ana Rita Dias; Joana Oliveira-Silva; Fatima Maia (Revista Salud y Bienestar Social, 2023)
Introduction. The COVID-19 pandemic has affected early child development. Early child development is part of the transformative plan for 2030, where all children should have the opportunity to reach their full developmental potential. The use of books could have benefits in many areas of children's development, going further than the literacy-related ones, as shown in most studies. Objective. Explore the various areas of children's development, use of books and summarize the evidence. Materials and Method. This is a literature review. The databases were used to capture the most important number of essential records: PubMed, Medline, Scielo, and Lilacs. Sources with critical documents of interest for this review were previously identified, influencing the option for a wide-ranging scoping literature review. Results. 468 eligible studies were identified after duplicates had been removed. Of these, 16 studies were selected for the final analysis. Interpretation. The use of books represents a tool rich in benefits to stimulate the correct development of children. It is a fundamental tool to be considered in contexts of mobility limitations and school closures imposed as protective measures during the pandemic. In both high- and middle-income countries, interventions focus on low- or middle-income groups, which is understood as a response to concerns about children's developmental delays. The use of books alone or in conjunction with other resources only benefits children; no adverse effect was reported in the literature. In a globalized world where technology is very important, printed books are still very important in places where technology hasn't caught up.